2003
DOI: 10.1177/107602960300900207
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Clinical Estimation of Perioperative Hemorrhage

Abstract: The purpose of this study was to assess the accuracy of estimated blood loss (EBL) as a reliable predictor of actual blood loss during orthopedic procedures. Between 1999 and 2002, 198 orthopedic cases were reviewed. A retrospective review compiled preoperative and postoperative demographic and laboratory data from the surgical patients. Estimated blood loss data was collected from the perioperative and anesthesia reports. Statistical analysis of EBL vs. change in hemoglobin yielded a correlation coefficient o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…This study does, however confirm the validity of EBL and its significance as it directly correlates as a predictor of change in hemoglobin. 8 In our study, we found that there was underestimation of blood loss in 48.1% of cases of abdominal hysterectomy and overestimation in 51.9%. Ganesan Ganesan Ram et al 3 in their study on blood loss in hip or knee replacement surgeries found that 70% of patients had their blood loss underestimated.…”
Section: Discussionmentioning
confidence: 78%
“…This study does, however confirm the validity of EBL and its significance as it directly correlates as a predictor of change in hemoglobin. 8 In our study, we found that there was underestimation of blood loss in 48.1% of cases of abdominal hysterectomy and overestimation in 51.9%. Ganesan Ganesan Ram et al 3 in their study on blood loss in hip or knee replacement surgeries found that 70% of patients had their blood loss underestimated.…”
Section: Discussionmentioning
confidence: 78%
“…Many anaesthetists relied on a combination of the above factors to reach the decision to transfuse. Some authors have used statistical models to predict changes in intraoperative Hb using preoperative Hb, estimated blood loss and intravenous fluids received with good results (Howe et al , 2003). Gross’s formula of maximum allowable blood loss based on weight, body habitus and preoperative Hb is widely used.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age in our study was 56 years, and 36 years in the patient group from Yoo et al 22 Haemoglobin drops have been suggested to be a better estimate of overall blood loss than intra-operative assessment, but in a large study of 198 orthopaedic patients undergoing major surgery, Howe et al demonstrated that clinical estimation of blood loss correlated well with actual change in peri-operative haemoglobin. 28,29 Perazzo et al showed that the mean Hb drop in 312 patients following THA was 2.6 g/dl, whereas Callaghan et al have shown it to be higher at 4.07 g/dl. 30,31 In this study haemoglobin values were recorded, but there was no data for comparison from other published literature evaluating blood loss in haemophilia patients, nor are there any guidelines in WHR documentation on Haemoglobin assessments.…”
Section: Discussionmentioning
confidence: 99%